On Two Banach-Type Fixed Points in Bipolar Metric Spaces - Yaé Ulrich Gaba; Maggie Aphane; Vizender Sihag (Abstract and Applied Analysis)
In this article, we propose two Banach-type fixed point theorems on bipolar metric spaces. More specifically, we look at covariant maps between bipolar metric spaces and consider iterates of the map involved. We also propose a generalization of the Banach fixed point result via Caristi-type arguments.